Penciptaan Tekstil Monumental pada Busana Ready To Wear Deluxe dengan Sumber Ide Jaranan Buto - Karellina, Stefani Cinthia; Arifiana, Deny; Nashikhah, Ma'rifatun; Nahari, Inty (Dinasti Research, 2025)
This research is an art creation research that focuses on monumental textiles with the source of inspiration, Jaranan Buto. The purposes of this research are (1) to describe the process of preparing ideas and concepts, (2) to describe and realize the results of the process of making the product, (3) to describe the presentation of the product. The methods used in this research are the methods of art creation with four phases, namely pre-design, design, realization and presentation or dissemination. The result of this research is a monumental textiles with buto puppet design as many as three designs. The monumental textiles are made by combining several techniques, namely, embroidery, beading, crochet, 3D application. The monumental textiles were applied to one part of the ready to wear deluxe tops for men and women.